Vertebral artery occlusion and oral contraceptives. Issue 6008 (28th February 1976) - Ask-Upmark, E; Bickerstaff, E R
Abstract : If vertebral artery occlusion occurs in degenerative arterial disease it is almost invariably left-sided, but in vertebral artery deficiency syndromes associated with oral contraceptives a striking preponderance of right-sided involvement has been shown. This observation adds support to the view that causes other than changes in the wall of the vessel at the site of occlusion must be sought as an explanation of the occlusion.